A critical examination of how AI-driven writing tools have impacted the content, style, and organization of foreign language undergraduates’ writing: A survey of lecturers - Ibrahim Abdallah Al-Shaboul; Rafat Mahmoud Al Rousan; Tahira Kalsoom; Nabil A-Awawdeh (Research Journal in Advanced Humanities, 2024)
This paper explores the impact of AI-powered writing tools on enhancing the writing structure, content, and style of foreign language undergraduates. The study included seven university lecturers (LEC1-7) in foreign languages, and gathered data through a series of semi-structured interviews. The views of the participating lecturers form the basis for the conclusions reached in this study, in comparison with the findings of previous studies, and was analysed using thematic analysis tools. The results indicated that the frequency of usage of the AI-powered writing-tools differed across the seven participating lecturers. Across all participants, Grammarly is the most commonly used tool, used by lecturers to conduct grammar and spelling checks on undergraduate assignments. This consistency in the use of Grammarly signifies the general respect and acknowledgment of the tool as a useful resource for improving the quality of undergraduates’ written assignments. Besides being a remarkable aid to undergraduates in the revision, editing, and paraphrasing of their papers and improving sentence coherence, QuillBot also plays a major role among the lecturers. The presence of ChatGPT in the most popular applications suggests its effectiveness in generating ideas and enhancing the logical structure of writing. Lecturers have seen how AI-powered writing-tools promote the development of ideas. However, some concerns also surface, such as the potential for dependence on these machines, which could hinder independent thought and worsen writing skills. On the other hand, the LEC3 was a neutral platform, taking into account the upsides and downsides of these tools. Also, LEC3 depicted the possibility of undergraduate students facing the concern of being overly dependent on technology, thereby inadvertently hindering the development of their reasoning and problem-solving skills. It is thus concluded that these AI-tools have the capacity to transform the writing skills of the students.